2023
DOI: 10.5455/msm.2023.35.28-32
|View full text |Cite
|
Sign up to set email alerts
|

Compassion Fatigue and Compassion Satisfaction in Pediatric Intensive Care Professionals

Abstract: Background: Paediatric ICU doctors and nurses’ quality of professional life is influenced by the intense emotions and distress experienced when caring for suffering children and their families. Objective: The aim of this study was to examine the prevalence of compassion satisfaction (CS) and compassion fatigue (CF) in Paediatric Intensive Care Units in Greece. Methods: Out of 147 intensive care professionals in public hospitals in Greece completed the ProQOL-V scale as well as a socio-demographic and professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
2
1
Order By: Relevance
“…Recent research has found that healthcare workers have experienced heightened levels of burnout and higher levels of compassion when compared with the pre-pandemic [4,10]. Our study did not find any statistically significant associations between CS, BO, or STS and gender and age.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…Recent research has found that healthcare workers have experienced heightened levels of burnout and higher levels of compassion when compared with the pre-pandemic [4,10]. Our study did not find any statistically significant associations between CS, BO, or STS and gender and age.…”
Section: Discussioncontrasting
confidence: 88%
“…Participants who indicated treating only pediatric patients showed the lowest BO and STS scores, while those who indicated caring for adult and pediatric patients reported the highest BO and STS scores. In contrast, Panagou et al [10] found moderate levels of BO and STS among providers treating pediatric Intensive Care Unit (ICU) patients, which was attributed to the severity of the patients being treated and the negative outcomes associated with pediatric patients in the ICU.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation